(untitled) (Gestión y Gerencia, 2024)
Teachers must rethink their daily practice in order to manage the curriculum in accordance with societal requirements and generate contributions for the common good and social development. In light of these premises, they must deploy an innovative managerial task with a view to facing the telos of digitalization, artificial intelligence, globalization and constant transformation resulting from science and technology to build the foundations for the humanistic progress of nations. In this sense, the study presents a hermeneusis on curriculum management with emphasis on the managerial action of teachers in their quest to build quality educational processes. The reflective understanding articulated from an interpretative paradigm and qualitative approach to expand the generation of theoretical constructs that project knowledge towards new horizons of reason. Finally, understood that curriculum management is a holistic managerial task that evokes processes, knowledge and pedagogical skills to guide a quality educational process in educational institutions.